Financial Literacy and Financial Planning for Retirement "Case Studies on Employees PT. Adhi by Tbk. (Persero)" - Wahyu Amin Candra; Surya Raharja (Jurnal Multidisiplin Madani, 2023)
The purpose of this study was to test the relationship between the level of financial literacy of PT. Adhi Karya Tbk (Persero) and its retirement plans.  The data used in this study is primary data from the results of the distribution of the questionnaire form to PT employees. Adhi Karya Tbk. (Persero). The method used in this study is a survey method that intends to analyze data through the description of the data that has been obtained. Hypothesis testing in this study used multiple linear analysis. The results prove that financial behavior has an influence on retirement financial planning, while financial knowledge and attitudes have no effect